Technological Change, Skill Demand, and Wage Inequality in Indonesia - Jong-Wha Lee; Dainn Wie (Asian Development Bank (ADB), 2013)
This paper examines the empirical implications of technological changes for skill demand and wage inequality in Indonesia. According to the National Labor Force Survey of Indonesia, the share of educated workers and wage skill premium increased significantly over 2003–2009 for overall industry and across the region. An analysis based on demand–supply framework suggests that demand shifts favoring skilled workers during the period. The decomposition of labor demand shifts shows that they were driven not only by reallocation of labor forces between industries but also by change within industries, particularly among formal workers, suggesting evidence of skill-biased technological changes. The empirical evidence from the data of manufacturing firms suggest that diffusion of new technologies through imported materials and foreign direct investment caused greater demand for skilled labor and higher wage inequality in the manufacturing sector.
hdl:11540/2328
Keywords: J24; J31; O15; O33; 330; skill-biased technological change; human capital; wage inequality; Technischer Fortschritt; Humankapital; Lohnstruktur; Qualifikation; Arbeitsnachfrage; Indonesien